Translation variations under legal constraints in the packaging information of Traditional Chinese herbal medicine sold in Malaysia - Liu, Yi; Yang, Qiuling; Hu, Yun (Routledge, 2025)
Chinese-English pharmaceutical-packaging translation facilitates the dissemination and acceptance of traditional Chinese medicines (TCMs) within the multilingual and multicultural context of Malaysia. However, awareness of TCMs beyond the Chinese community remains limited due to major factors including legal constraints imposed by drug regulatory authorities and challenges in translating product names and indications. Therefore, this article investigates the translation of packaging information for TCMs sold in Malaysia, where multiple cultures and languages interact. The study anchors itself on the translation procedures proposed by Vinay and Darbelnet (1958/1995). The article adopts a descriptive and comparative approach based on a sample of 36 TCM products obtained from the official websites of two local pharmacies. It reflects on how the legal requirements of the National Pharmaceutical Regulatory Agency (NPRA) impact what can or cannot be included in packaging. In essence, it examines how translation decisions are influenced by legal constraints and discusses the value of different translation approaches in light of these constraints. The significance of studying TCM translation under legal constraints in a specific market lies in ensuring regulatory compliance, safeguarding consumer safety, facilitating market access, preserving cultural sensitivity, and upholding professional standards and ethical practices within the Chinese-English pharmaceutical-packaging translation practice.